2009
DOI: 10.1007/s10902-009-9166-1
|View full text |Cite
|
Sign up to set email alerts
|

Momentary Happiness: The Role of Psychological Need Satisfaction

Abstract: Subjective well-being, Happiness, Self-determination theory, Psychological needs,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 26 publications
4
44
0
Order By: Relevance
“…Similarly, the need balance model was minimally predictive of well-being outcomes of collegiate athletes and held no predictive ability in Milyavskaya and colleagues (2009) Gunnell et al, 2011;Hofer & Busch, 2011;Howell et al, 2011;Milyavskaya & Koestner, 2011;Sheldon & Niemiec, 2006;Wilson et al, 2006). Perhaps, balance across satisfaction of the three needs is not an important predictor in children and adolescents because, as we have seen with the present study, the predictive ability of satisfaction of some needs varies as a function of development.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, the need balance model was minimally predictive of well-being outcomes of collegiate athletes and held no predictive ability in Milyavskaya and colleagues (2009) Gunnell et al, 2011;Hofer & Busch, 2011;Howell et al, 2011;Milyavskaya & Koestner, 2011;Sheldon & Niemiec, 2006;Wilson et al, 2006). Perhaps, balance across satisfaction of the three needs is not an important predictor in children and adolescents because, as we have seen with the present study, the predictive ability of satisfaction of some needs varies as a function of development.…”
Section: Discussionmentioning
confidence: 98%
“…There has been much empirical evidence to support the association between satisfaction of intrinsic needs and various indices of psychological well-being, such as momentary happiness (Howell, et al, 2011), vitality, positive affect (Adie, Duda, & Ntoumanis, 2012;Bartholomew, Ntoumanis, Ryan, Bosch, & Thogersen-Ntoumani, 2011;Milyavskaya & Koestner, 2011;Reis, Sheldon, Gable, Roscoe, & Ryan, 2000;Sheldon, Ryan, & Reis, 1996), self-esteem (Amarose, Anderson-Butcher, & Cooper, 2009;Heppner, et al, 2008;Ilardi, Leone, Kasser, & Ryan, 1993), relationship functioning and quality (Patrick, Knee, Canevello, & Lonsbary, 2007), and security of attachment (La Guardia, Ryan, Couchman, & Deci, 2000). Furthermore, there is empirical evidence to suggest that when needs are not fulfilled, negative psychological consequences result such as unhappiness, dissatisfaction with life, lack of selfactualization (Meyer, Enstrom, Harstveit, Bowles, & Beevers, 2007), disordered eating, burnout, depression, anxiety, negative affect, and physical symptoms (Baard, Deci, & Ryan, 2004;Bartholomew et al, 2011;Quested et al, 2011;Thøgersen-Ntoumani, Ntoumanis, & Nikitaras, 2010).…”
Section: Self-determination Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Big Five Personality Model, Tkach, and Lyubomirsky (2006) found out that personality traits can mediate happiness, especially extraversion. Howell, Chenot, Hill, and Howell (2011) concluded that satisfaction of daily psychological needs results to happiness. As children mainly focuses on their peers and family relationship (Holder & Coleman, 2007) as similar with the adolescents (Chen & Lu, 2009) and romantic relationship for married adults (Demir, 2008;Demir, 2010) while best friend and mother relationship arouse for single adults (Demir, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that "happiness is the sum total of all particular pleasures" of one sort or another has been explored in the past 20 years under various names, e.g., affective happiness (Helliwell, Layard, & Sachs, 2012), momentary happiness (Howell, Chenot, Hill, & Howell, 2011) hedonia (Deci & Ryan, 2008), hedonic enjoyment (Waterman, Schwartz, & Conti, 2008, hedonic happiness (Seligman, 2002) and objective happiness (Kahneman, 1999). The pleasures are typically regarded as time-limited or transitory and somehow connected to particular feelings or experiences.…”
Section: Pleasurementioning
confidence: 99%